Library and Information Science Research in the 21st Century: A guide for practising librarians and students - Lawal, Ibironke O. (Oxford: Chandos Publishing, 2009)
The book provides a general overview of library and information science in the 21st century. Topics covered include library studies, information management, internet, knowledge management, publishing and intellectual property.
Includes bibliographical references and Index
lje 19/06/13; rpm 02/07/13
Loans
Keywords: Library Science -- Research; Information science -- Research